Zirconium-titanium mixed coated perovskite quantum dot and preparation method thereof

Through the zirconium-titanium hybrid coating technology, a double cladding layer is formed, which solves the degradation problem of perovskite quantum dots in oxygen, water, heat and light environments, and significantly improves its stability and luminous performance.

CN119709175APending Publication Date: 2025-03-28WUXI UTMOST LIGHT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311251680.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Perovskite quantum dot materials are prone to degradation after contacting oxygen, water, thermal atmosphere, and light environment, resulting in a decrease in luminous performance and poor stability.

Method used

Using the method of mixed zirconium-titanium coating, a double cladding layer is formed on the surface of perovskite quantum dots. Through a specific proportion of zirconium and titanium, the ligand on the surface of perovskite quantum dots is closely combined with the ligand on the surface of perovskite quantum dots to improve its stability and luminescence performance.

Benefits of technology

It effectively improves the stability and luminous performance of perovskite quantum dots in polar environments and high temperatures, avoids the damage to the material by the polar radicals of the adhesive film, and enhances the material's anti-aging ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709175A_ABST
    Figure CN119709175A_ABST
Patent Text Reader

Abstract

The invention discloses a zirconium-titanium mixed and coated perovskite quantum dot and a preparation method thereof, and the preparation method comprises the steps: in a normal temperature environment, adding a zirconium source, a titanium source and an organic acid into an organic solvent, and fully mixing to obtain a first mixed solution; in a normal-temperature environment, perovskite quantum dots are added into the first mixed solution, and a first reaction solution is obtained after a reaction; and separating the first reaction liquid to obtain the zirconium-titanium mixed and coated perovskite quantum dots. According to the preparation method, through dual coating of the zirconium-titanium compound, a coating layer is formed on the surface of the perovskite quantum dot, so that ligands on the surface of the perovskite quantum dot are tightly combined, the effects of improving the luminescence performance, stabilizing the crystal structure and improving the stability are achieved, and the preparation method for improving the polarity tolerance degree of the perovskite quantum dot in the adhesive film is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The patent of this invention belongs to the field of perovskite quantum dot materials, and specifically relates to a zirconium-titanium mixed-coated perovskite quantum dot and a preparation method thereof. Background Art

[0002] Lead halide perovskites have become key research materials in the field of optoelectronics due to their adjustable band gap, high photoluminescence efficiency, and high-purity luminescent color. Perovskite quantum dot materials are prone to degradation after exposure to oxygen, water, heat, and light environments, making it difficult to maintain good luminescence performance and poor material stability. In practical applications, perovskite components require more protection from adhesive films. However, there are a large number of polar free radicals in the crosslinkers and coupling agents in the adhesive film, which cause great damage to the luminescence performance and stability of perovskite quantum dots. In order to improve the stability of perovskite quantum dots, the use of inorganic materials zirconium, titanium, and silicon to encapsulate perovskite quantum dots is one of the commonly used and effective methods. Fan et al. encapsulated the CsPbBr3@Cs4PbBr6 core-shell structure using a silicon matrix. The silicon oxide matrix isolated the CsPbBr3@Cs4PbBr6 core-shell structure from the external environment, significantly improving the stability of perovskite in high temperature, high humidity, and blue light irradiation environments.

[0003] Such coating methods can obtain perovskite quantum dot materials with better stability, but they are still far from practical applications due to a series of problems exposed in the film polar free radicals, water environment, and thermal atmosphere. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is that the perovskite quantum dot materials in the prior art are easily degraded after being exposed to oxygen environment, water environment, thermal atmosphere, and light environment, and it is difficult to maintain good luminescence performance and the material has poor stability, thereby providing a zirconium-titanium mixed coated perovskite quantum dot and a preparation method thereof.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] In a room temperature environment, a zirconium source, a titanium source, and an organic acid are added to an organic solvent and mixed thoroughly to obtain a first mixed solution; the room temperature generally refers to room temperature, for example, a temperature environment of 20 to 25° C.;

[0007] Adding perovskite quantum dots to the first mixed solution at room temperature to obtain a first reaction solution after reaction;

[0008] The zirconium-titanium mixed perovskite quantum dots are separated from the first reaction solution. The perovskite quantum dots can be FA a MA b Cs 1-a-b Pb1-c-d-e-f Zn c Cd d Cu e Mg f Cl m Br n I 3-m-n , where 0≤a≤1, 0≤b≤1, a+b≤1, 0≤c≤1, 0≤d≤1, 0≤e≤1, 0≤f≤1, c+d+e+f≤1, 0≤m≤3, 0≤n≤3, m+n≤3, for example, FAPbBr3, CsPbBr3 or CsPbBr 1.2 I 1.8 Any one or at least two of the following.

[0009] Furthermore, the molar ratio of the zirconium source to the titanium source is 1:(1-2); and the molar ratio of the perovskite quantum dots to the zirconium source is 1:(1-1.5).

[0010] The organic acid includes at least one of formic acid, acetic acid, propionic acid, butyric acid, octanoic acid, adipic acid, oxalic acid, malonic acid, succinic acid, and acrylic acid.

[0011] The pH of the first mixed solution is 4-6.

[0012] The zirconium source includes at least one of zirconium n-butoxide, zirconium n-propoxide, and zirconium tert-butoxide;

[0013] The titanium source includes at least one of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate;

[0014] The organic solvent includes at least one of toluene, dimethyl sulfoxide, dimethylformamide, tetrahydrofuran, n-hexane, cyclohexane and dichloromethane.

[0015] Furthermore, the zirconium source is zirconium n-butoxide, the titanium source is tetrabutyl titanate, and the organic solvent is toluene.

[0016] The mixing time of the zirconium source, titanium source and organic acid in the organic solvent is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h, and the stirring speed is 300-800rpm, for example, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm.

[0017] The reaction time for obtaining the first reaction liquid is 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, and the stirring speed is 300-800rpm, for example, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm.

[0018] The present invention also provides a zirconium-titanium mixed-coated perovskite quantum dot, characterized in that it is prepared by the above-mentioned preparation method.

[0019] The technical solution of the present invention has the following advantages:

[0020] (2) The present invention forms a coating layer on the surface of perovskite quantum dots through double coating with zirconium-titanium compounds, so that the surface ligands of the perovskite quantum dots are tightly bound, which plays a role in improving the luminescence performance, stabilizing the crystal structure, and improving the stability, and provides a preparation method for improving the polarity tolerance of perovskite quantum dots in the film.

[0021] (3) The present invention adopts a specific ratio of zirconium and titanium, and the coated surface does not need to be subjected to additional water environment hydrolysis, and does not need to be heated, thereby avoiding the undesirable phenomenon of destroying the crystal structure of quantum dots and reducing the luminous efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 is the initial fluorescence efficiency of the quantum dots in Example 1 and Comparative Example 1 after film coating;

[0024] Figure 2 The fluorescence efficiency change curves of the quantum dots in Example 1 and Comparative Example 1 after film coating in the aging test. DETAILED DESCRIPTION

[0025] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0026] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional experimental steps or conditions described in the literature in the art.

[0027] Example 1

[0028] This embodiment provides a zirconium-titanium mixed-coated perovskite quantum dot, and the specific preparation method thereof is as follows:

[0029] (1) Weigh 3.2582 g of cesium carbonate and add it to a mixed solution of 20 mL of oleic acid and 20 mL of 1-octadecene. Place the mixture on a magnetic stirring table and heat at 120° C. under vacuum and stir for 1 h. Then, introduce N2 and raise the temperature to 150° C. until the solution is clear and reacted completely to obtain a precursor solution.

[0030] Weigh 0.734g of lead bromide, put it into a mixed solution of 5mL of oleic acid, 5mL of oleylamine and 20mL of 1-octadecene, place it on a magnetic stirring table, heat it at 120℃, evacuate and stir for 1h, then introduce N2, raise the temperature to 180℃, and react for 30min. Take 1mL of the precursor solution and inject it, react for 10s and cool it in an ice bath. After the ice bath, add ethyl acetate to the reaction solution for washing, and disperse it in 10mL of toluene to obtain a toluene solution of CsPbBr3 quantum dots.

[0031] (2) 0.0383 g zirconium n-butoxide, 0.034 g tetrabutyl titanate, and 0.006 g acetic acid were added to 5 ml toluene and stirred at room temperature for 60 min, and then 5 ml CsPbBr3 quantum dot toluene solution was added. After stirring at room temperature for 3 h, the supernatant was removed by centrifugation to obtain the zirconium-titanium mixed coated perovskite quantum dots, specifically CsPbBr3 quantum dots coated with zirconium n-butoxide-tetrabutyl titanate, and the precipitate was dispersed in 5 mL toluene solution.

[0032] Example 2

[0033] This embodiment provides a zirconium-titanium mixed coated perovskite quantum dot, which differs from Embodiment 1 in that in step (2), 0.0383 g of zirconium n-butoxide is replaced by 0.0327 g of zirconium n-propoxide, and 0.034 g of tetrabutyl titanate is replaced by 0.0284 g of isopropyl titanate.

[0034] Example 3

[0035] This embodiment provides a zirconium-titanium mixed-coated perovskite quantum dot, which is different from Embodiment 1 in that the solvent of the system is changed to dichloromethane.

[0036] Comparative Example 1

[0037] This comparative example provides a perovskite quantum dot, which differs from Example 1 in that step (2) is not performed.

[0038] Comparative Example 2

[0039] This comparative example provides a perovskite quantum dot, which differs from Example 1 in that in step (2), 0.0383 g of zirconium n-butoxide is replaced with 0.0766 g of zirconium n-butoxide, and tetrabutyl titanate is not added.

[0040] Comparative Example 3

[0041] This comparative example provides a perovskite quantum dot, which is different from Example 1 in that 0.034 g of tetrabutyl titanate in step (2) is replaced by 0.068 g of tetrabutyl titanate, and zirconium n-butoxide is not added.

[0042] Comparative Example 4

[0043] This comparative example provides a perovskite quantum dot, which is different from Example 1 in that in step (2), stirring at room temperature for 3 hours is changed to heating and maintaining stirring at 80° C. for 3 hours.

[0044] Comparative Example 5

[0045] This comparative example provides a perovskite quantum dot, which is different from Example 1 in that in step (2), 0.034 g of tetrabutyl titanate is replaced with 0.0233 g of barium sulfate, that is, the comparative example uses a combination of zirconium and barium.

[0046] Test example

[0047] The quantum dots obtained in the examples and comparative examples were coated with adhesive films, having:

[0048] (1) Weigh 200 g of PS (polystyrene) masterbatch base material in a ziplock bag.

[0049] (2) The quantum dots need to be dissolved in n-hexane for use.

[0050] (3) Add the mixed quantum dots to the masterbatch base material of step (1), seal it and shake it evenly, add 1.4g 1.0μm silicone diffusion particles and 1.6g antioxidant and shake it evenly, and set aside.

[0051] (5) Add the mixed base material with quantum dots into an injection molding machine to extrude a film, which is the quantum dots coated with the film.

[0052] The initial fluorescence efficiency of the quantum dots obtained from the examples and comparative examples after film coating was tested respectively (fluorescence efficiency = (red quantum dot absorption peak area + green quantum dot absorption peak area) / (blue backlight peak area - blue peak area that is not absorbed by the quantum dot film) × 100%), and a double 85 aging test was performed. The double 85 aging test is specifically to place the film in a constant temperature and humidity aging test box, set the box temperature to 85°C, and the relative humidity to 85% RH (RH represents relative humidity). The film was taken out at different time periods for fluorescence efficiency testing. The results are as follows. Figure 1 , Figure 2 And as shown in Table 1.

[0053] Table 1 Initial fluorescence efficiency and fluorescence efficiency after aging of Examples and Comparative Examples

[0054]

[0055] As can be seen from the above table, the embodiments using the technical solution of the present application have a very high initial fluorescence efficiency, and the fluorescence efficiency remains good after aging and storage for 10 days, indicating that the embodiments of the present application can effectively resist the polar free radicals of the film, the water environment, and the thermal atmosphere. Among them, embodiment 1 is better than embodiment 3, because the polarity of dichloromethane is greater than that of toluene, and compared with toluene, it accelerates the reaction speed to a certain extent, which is not conducive to the coating reaction. Comparative Example 1 is a quantum dot without zirconium and titanium coating. It can be seen that its initial fluorescence efficiency is clearly lower than that of Example 1, and the fluorescence efficiency loss after aging is extremely large; Comparative Example 2 is a quantum dot coated with zirconium with the same molar amount of zirconium + titanium as in Example 1, and Comparative Example 3 is a quantum dot coated with the same molar amount of zirconium + titanium as in Example 1. It can be seen that its initial fluorescence efficiency and fluorescence efficiency after aging are not as good as the technical solution of Example 1; Comparative Example 4 does not react at room temperature, but at 80°C. When the temperature rises, the quantum dots cause the luminescence intensity to weaken, that is, the fluorescence "thermal quenching" phenomenon, and affects the anti-aging performance. Its initial fluorescence efficiency is even lower than that of Comparative Example 1, and the fluorescence efficiency loss after aging is very large; Comparative Example 5 is coated with zirconium + barium, and barium is also a commonly used coating material for quantum dots. However, from the effect, it can be seen that its initial fluorescence efficiency is similar to that of Comparative Example 2, which is much lower than that of Example 1, and the fluorescence efficiency after aging is even worse than that of Comparative Example 2, indicating that not all coating materials can be coated together. Inappropriate selection of materials will affect the coating effect.

[0056] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing zirconium-titanium mixed-coated perovskite quantum dots, characterized in that: include: At room temperature, a zirconium source, a titanium source and an organic acid are added into an organic solvent and mixed thoroughly to obtain a first mixed solution; Adding perovskite quantum dots to the first mixed solution at room temperature to obtain a first reaction solution after reaction; The zirconium-titanium mixed-coated perovskite quantum dots are separated from the first reaction solution.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the zirconium source to the titanium source is 1:(1-2); the molar ratio of the perovskite quantum dots to the zirconium source is 1:(1-1.5).

3. The preparation method according to claim 1 or 2, characterized in that: The organic acid includes at least one of formic acid, acetic acid, propionic acid, butyric acid, octanoic acid, adipic acid, oxalic acid, malonic acid, succinic acid, and acrylic acid.

4. The preparation method according to claim 3, characterized in that: The pH of the first mixed solution is 4-6.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The zirconium source includes at least one of zirconium n-butoxide, zirconium n-propoxide, and zirconium tert-butoxide; The titanium source includes at least one of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate; The organic solvent includes at least one of toluene, dimethyl sulfoxide, dimethylformamide, tetrahydrofuran, n-hexane, cyclohexane and dichloromethane.

6. The preparation method according to claim 5, characterized in that: The zirconium source is zirconium n-butoxide, the titanium source is tetrabutyl titanate, and the organic solvent is toluene.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The mixing time of the zirconium source, titanium source and organic acid in the organic solvent is 1-3 hours, and the stirring speed is 300-800 rpm.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The reaction time of the first reaction liquid obtained after the reaction is 2-5h, and the stirring speed is 300-800rpm.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The method for separating the zirconium-titanium mixed-coated perovskite quantum dots from the first reaction solution is to remove the supernatant by centrifugal separation.

10. A zirconium-titanium mixed-coated perovskite quantum dot, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.